Fractional‐order back‐stepping sliding‐mode torque control for a wind energy conversion system. Issue 4 (19th December 2018) - Talebi, Jalal; Ganjefar, Soheil
Abstract : At below‐rated wind speeds, the main goal of a controller design is to maximize power coefficient and consequently captured power. Due to nonlinearities and uncertainties in wind turbine systems and rapid variations in the wind speed profiles, the need for more effective and robust controllers is inevitable. To optimize the captured power, the rotor angular speed must track the time variable reference value that requires fast reactions of the designed controller. In this article, an advanced controller called a back‐stepping sliding‐mode controller was proposed to improve the turbine efficiency at a below‐rated wind speed. The controller was designed based on the combination of the back‐stepping sliding mode approach and fractional order calculus. The stability of the proposed controller is analyzed using the Lyapunov stability criterion. Finally, numerical simulation results are presented and compared with integer order, back‐stepping sliding mode control to illustrate the effectiveness of the proposed method. The simulation results demonstrated that the proposed controller had a good transition response, a low tracking error, and a very fast reaction against rapid variations in the wind speed in comparison to the back‐stepping sliding mode controller. © 2018 American Institute of Chemical Engineers Environ Prog, 38:e13110, 2019